Land-use evaluation and utilization advice research on debris flow disaster deposit area - Yang, Shun; Pan, Huali; She, Tao; Jiao, Jiaxuan; Tian, You; Chen, Kun (Frontiers in Earth Science, 2022)
The upstream Fujiang River are famous for their high mountains and narrow canyons, which results in a conflict of interest between local residents and land use. To make good use of precious land resources is a meaningful work for local people and government. Therefore, field surveys and theoretical analysis were carried out in the upstream Fujiang River to explore the land-use evaluation and utilization advice. Firstly, we analyzed the factors which affect the land use of debris flow depositional area. Secondly, we chose the factors of soil fertility quality, soil particle conservation, and the geological engineering condition to set up the land-use evaluation method. Thirdly, through index classification, we give the planting type, land-use type, construction type respectively, according to grading and assignment value for each factor, we built the debris flow disaster-prone land utilization mode R by using an analytical hierarchy process method. Lastly, taking Huangjiaba village as an example, based on the debris flow disaster land-use evaluation method and debris flow hazard evaluation, we identified four land-use scenarios. The results show that the value of the four scenarios is between 1.00 and 4.00, the four scenarios utilization advices are given based on each R-value and Huangjiaba natural condition. It also obtained that the developmental tendencies of the debris flow disaster areas appear to deposit recently, the frequency of debris-flow activity is evolving from high to stable, on making good use of debris flow deposit fan’s usage is necessary to explore the disaster prone land and avoid disaster loss. Further studies need to systematically consider more factors to evaluate debris flow and disaster-prone land utilization, which can provide a reference for the rural space planning and revitalization for the local government.